A revision of the family Cerococcidae Balachowsky (Hemiptera: Sternorrhyncha, Coccomorpha) with particular reference to species from the Afrotropical, western Palaearctic and western Oriental Regions, with the revival of Antecerococcus Green and description of a new genus and fifteen new species, and with ten new synonomies - Hodgson, Chris J.; Williams, Douglas J. (Zootaxa, 2016)
The scale insect family Cerococcidae (Hemiptera: Coccomorpha) or false pit scales was last revised during the 1970s and 1980s. At that time, it included three genera, Asterococcus Borchsenius, Cerococcus Comstock and Solenophora Maskell, and a total of 69 species. The present revision concentrates on species known from the western Palaearctic, western Oriental and Afrotropical Regions but includes notes on all known cerococcid species. Within the three geographical areas principally studied here, all known species are described and illustrated based on the adult females, including 13 new species. During this study, a new morphological character was discovered on the venter of the anal lobes that is taxonomically important and which is referred to as the anteroventral sclerotization. It was found that the anteroventral sclerotization was present in most species from the main study areas, but was absent from all species in the Nearctic and from many in the Australasian and Neotropical Regions as well. As the type species of Cerococcus is C. quercus Comstock from the Nearctic, the genus Antecerococcus Green, revived status (type species Cerococcus punctiferus Green) was resurrected to take all species with an anteroventral sclerotization. Resurrection of Antecerococcus means that names of genera previously synonymised with Cerococcus are now junior synonyms of Antecerococcus, e.g., Phenacobryum Cockerell, syn. nov., Amelococcus Marchal, syn. nov., Cercococcus Scott, syn. nov. and Coricoccus Mahdihassan, syn. nov. As a range of other characters also were found to support this division (such as absence of setae along inner margin of each anal lobe and presence of a ventral seta posteriorly on each lobe), the genera in Cerococcidae can be divided into two groups, those with an anteroventral sclerotization (Antecerococcus and probably Solenophora) and those without (Asterococcus and Cerococcus). As part of this revision, it was found necessary to consider the morphological limits of all current genera, including those from outside the western Palaearctic, western Oriental and Afrotropical Regions. This resulted in a new genus, Cerochiton Hodgson & Williams, gen. nov., with three species from the Oriental Region. This genus also falls within the Cerococcus-group of genera. In addition, it was found that, with the inclusion of As. ovoides (Cockerell) from South Africa, Asterococcus was not morphologically monophyletic and so this species has been transferred to Antecerococcus as Antecerococcus ovoides (Cockerell), comb. nov. The following revived combinations are included: Antecerococcus bryoides Maskell and A. stellatus Maskell. In addition, the following Cerococcus species have been transferred to Antecerococcus as comb. nov.: Cerococcus albospicatus Green, C. ankaratrae Mamet, C. asparagi Joubert, C. camarai Neves, C. cistarum Balachowsky, C. cliffortiae Joubert, C. cycliger Goux, C. dumonti Vayssière, C. fradei Castel-Branco, C. gabonensis Lambdin, C. gallicolus Mamet, C. intermedius Balachowsky, C. laniger Goux, C. longipilosus Archangelskaya, C. madagascariensis Mamet, C. multipororum Lambdin & Kosztarab, C. oranensis Balachowsky, C. ornatus Green, C. passerinae Brain, C. perowskiae Archangelskaya, C. philippiae Lambdin & Kosztarab, C. pileae Mamet, C. pocilliferus Neves, C. polyporus Matesova, C. roseus Green, C. royenae Brain, C. ruber Balachowsky, C. steppicus Balachowsky and C. theydoni Hall. The following have also been transferred to Antecerococcus as comb. nov.: Amelococcus alluaudi Marchal, Cercococcus eremobius Scott, Eriococcus paradoxus indica Maskell, Phenacobryum indigoferae Borchsenius and Pollinia ovoides Cockerell. Two further undescribed species were discovered, one from Mexico and the other from Java, and a number of synonyms were found of names that are now all in Antecerococcus, as follows: Cerococcus camarai Neves is a junior synonym of Cerococcus intermedius Balachowsky, syn. nov.; Cerococcus cycliger Goux is a junior synonym of Cerococcus intermedius Balachowsky, syn. nov.; Phenacobryum indigoferae Borchsenius is a junior synonym of Cerococcus roseus Green, syn. nov.; Cerococcus multipororum Lambdin is a junior synonym of Cerococcus fradei Castel-Branco, syn. nov.; Cercococcus polyporus Matesova is a junior synonym of Cerococcus perowskiae Archangelskaya, syn. nov., and Antecerococcus punctiferus Green is a junior synonym of Cerococcus paradoxus Maskell, syn. nov. In addition, the following new species have been described: Antecerococcus andamanensis Hodgson & Williams, from the Andaman Islands; Antecerococcus capensis Hodgson & Williams, from South Africa; Antecerococcus delottoi Hodgson & Williams, from Kenya; Antecerococcus hilli Hodgson & Williams, from The Seychelles; Antecerococcus insleyae Hodgson & Williams, from South Africa; Antecerococcus kakemegae Hodgson & Williams, from Kenya; Antecerococcus keralae Hodgson & Williams, from southern India; Antecerococcus kurraensis Hodgson & Williams, from Nigeria; Antecerococcus muntingi Hodgson & Williams, from South Africa; Antecerococcus oumeensis Hodgson & Williams, from Ivory Coast; Antecerococcus sparsiporus Hodgson & Williams, from from South Africa; Antecerococcus thesii Hodgson & Williams from South Africa; Antecerococcus yemenicus Hodgson & Williams, from Yemen; Cerochiton bernardi Hodgson & Williams, from Java, and Cerococcus asteris Hodgson & Williams, from Mexico. Thus, at the end of this study, the family Cerococcidae includes five genera and 80 species (Antecerococcus with 55 species (13 of them new), Asterococcus with eight species, Cerochiton with three species (one of them new), Cerococcus with 13 species (1 of them new and including two unplaced species), and Solenophora with one species). Keys are provided for the separation of the five genera and also for the species in each genus based on adult female morphology. Lectotypes have been designated for Cerococcus asparagi Joubert, C camarai Neves, C. cistarum Balachowsky, C. cliffortiae Joubert, C. coffeae Vayssière, C. cycliger Goux, C. dumonti Vayssière, C. hibisci Green, C. intermedius Balachowsky, C. laniger Goux, C. pocilliferus Neves, C. royenae Brain and C. ruber Balachowsky, and for Cercococcus eremobius Scott and Solenophora coloradensis Cockerell. In addition, it was found that the lectotype of Eriococcus paradoxus Maskell (now Antecerococcus paradoxus) had been designated based on a specimen of Eriococcus paradoxus indica Maskell (now Antecerococcus indicus). This designation has been revoked and new lectotypes for Eriococcus paradoxus and Eriococcus paradoxus indica have been designated. Following the taxonomic section, the geographic distribution of each genus is briefly discussed. Asterococcus (with the removal of A. ovoides) is now restricted to the Oriental Region; Cerochiton is restricted to the southern part of the Oriental Region; Cerococcus appears to be restricted to Central and North America, while Antecerococcus has a world-wide distribution but is most abundant in the western Palaearctic, western Oriental and Afrotropical Regions. The single species now in Solenophora is only known from New Zealand. Two species, “Cerococcus” indonesiensis Lambdin & Kosztarab and “Cerococcus” michaeli Lambdin do not appear to belong to Cerococcus, but are being left there pending further studies and are referred to here as “unplaced species”.